Preparation, Characterization And Evaluation Of Daucus Carota For Pharmacological Activity As Potential Hepatoprotective Agents - Shreyash Tripathi; Dr.Sanjay Bhawar (Revista Electronica de Veterinaria, 2024)
The scope of this investigation includes an investigation into the hepatoprotective properties of an extract of Daucus carota, also known as carrot. Following the completion of the phytochemical examination, it was discovered that the sample included a considerable amount of carotenoids, flavonoids, and polyphenols. The results of experiments that were conducted in vitro indicated that the extract offers a substantial level of protection against the oxidative damage that can be caused to liver cells. There was a decrease in the levels of liver enzymes, as well as an improvement in the histological features of the liver, according to research that was conducted in vivo using a rat model. According to these data, it would appear that the extract of Daucus carota has the potential to be an effective natural hepatoprotective agent. This is the conclusion that can be drawn from the findings.